2013
DOI: 10.2147/ijwh.s40685
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for disclosure of gender to pregnant women during prenatal ultrasonography

Abstract: BackgroundThe objective of this study was to determine the proportion of women who want to know fetal gender on antenatal ultrasonography and the reasons behind this.MethodsA descriptive, cross-sectional study was carried out between March 10, 2012 and September 10, 2012 at two tertiary care hospitals (Dow University Hospital, Ojha Campus, and Lady Dufferin Hospital) in Karachi. In total, 223 pregnant women who attended the antenatal clinic and gave their consent were included in the study. Information was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
3
16
1
Order By: Relevance
“…2 Less preference of males and higher rate of not showing gender preference by pregnant women in our study may be due to us having more literate and educated women. We did not found relationship between education status of women and preference of gender of fetuses, contrary to our finding Yasmin 16 from eastern India had found that women of lower education status had more preference of gender of fetuses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2 Less preference of males and higher rate of not showing gender preference by pregnant women in our study may be due to us having more literate and educated women. We did not found relationship between education status of women and preference of gender of fetuses, contrary to our finding Yasmin 16 from eastern India had found that women of lower education status had more preference of gender of fetuses.…”
Section: Discussioncontrasting
confidence: 99%
“…A study from eastern rural area of Nepal, which was done among the non-pregnant women found that 64.4% of them wished to have a son as a first child. 16 There is paucity of studies of gender preference among pregnant women in our country. However, a study by Uprety 4 showed that males were preferred in the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the reason for women wanting to know the sex was almost unanimously described by physicians as related to curiosity and preparation for the newborn. These findings are similar to expectations reported from USA, the Netherlands and Pakistan , but in contrast to reports from Nigeria , where sex preference has been reported to be the main reason for expectant parents’ request for sex determination. Interestingly, our results are also in stark contrast to those of a study undertaken in the neighbouring country Uganda, where the participating radiologists and sonographers unanimously expressed fears that disclosing the sex at ultrasound may lead to selective abortion if the pregnant woman wanted the opposite sex .…”
Section: Discussionmentioning
confidence: 99%
“… 1 This practice is tolerated because there is no evidence or scientifically proven harm to the fetus. 1 , 2 Gender identification can be done by ultrasonography more reliably from 16 weeks of pregnancy, 1 3 and by the 20th week of gestation, the accuracy is close to 97%. 2 …”
Section: Introductionmentioning
confidence: 95%